KONTRIBUSI ORGANISASI DASAWISMA DALAM MENGUATKAN KARAKTER RELIGIUS DAN UKHUWAH ISLAMIYAH PADA ANGGOTA DASAWISMA BULAY KABUPATEN PAMEKASAN - Afifah Dwi Faradilla; Nor Hasan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the contribution of the Dasawisma organization in strengthening religious character and Islamic brotherhood among the people of Bulay Village, Galis District, Pamekasan Regency. As a community-based organization, Dasawisma has proven to focus not only on family empowerment but also on providing a platform for religious and social development. The research method used was qualitative with a descriptive approach, through observation, interviews, and documentation. The results indicate that Dasawisma activities, such as regular religious study groups, prayer gatherings, social activities, and commemorations of Islamic holidays, play a significant role in instilling religious values, strengthening solidarity, and strengthening relationships among community members. Thus, Dasawisma serves as an effective platform for instilling Islamic values that strengthen morals and maintain social harmony.